Clinico-Epidemiological Study Of Factors Associated With Pregnancy Induced Hypertension - Amir Ali; Yunus Mohd; Islam H. M (Wolters Kluwer Medknow Publications, 1998)
Research Question: What are the factors responsible for pregnancy induced hypertension. Objectives: To determine whether maternal, demographic, clinical and socio-economic characteristics are predictive of hypertension associated with pregnancy. Study design: Cross â€" Sectional. Participants: 728 hypertensive pregnant mothers attending the ante-natal clinic and admitted to the inpatient department of obstetric unit. Study Variables: Maternal, demographic and socio-economic characteristics. Outcome variable: Hypertension associated with pregnancy. Statistical analysis: Percentages and proportions. Results: The relative incidence of pregnancy induced hypertension was 71.29%. The critical evaluation of social and demographic characteristics of 519 cases of pregnancy induced hypertension revealed that nulliparous, young women (15-25 years) belonging to low socio-economic group with lower literacy status and higher house hold work load are more vulnerable to develop pregnancy induced hypertension. Inadequate diet having low protein, rich carbohydrate and extra salt intake played a crucial role in the development of pregnancy induced hypertension. Conclusions: i) since the nulliparous and younger women are vulnerable to develop pregnancy induced hypertension, the age at first pregnancy be reasonably delayed. ii) Balanced diet is to be ensured through appropriate nutrition education and within t he resources of the family. iii) The heavy household work is to be avoided and adequate rest and sleep be ensured in those who are at risk of developing pregnancy induced hypertension.